Myeloid KLF2 Regulates the Host Response to Polymicrobial Infection and Endotoxic Shock - Mc Manus, Ross (My University, 2011)
Precise control of myeloid cell activation is required for optimal host defense. However, this activation process must be under exquisite control to prevent uncontrolled inflammation. Herein, we identify the Kruppel-like transcription factor 2 (KLF2) as a potent regulator of myeloid cell activation in vivo. Exposure of myeloid cells to hypoxia and/or bacterial products reduced KLF2 expression while inducing hypoxia indusable factor-1 ? (HIF-1 ? ), findings that were recapitulated in human septic patients. Myeloid KLF2 was found to be a potent inhibitor of nuclear factor- kappaB (NF ? B)-dependent HIF-1 ? transcription and, consequently, a critical determinant of outcome in models of polymicrobial infection and endotoxemia. Collectively, these observations identify KLF2 as a tonic repressor of myeloid cell activation in vivo and an essential regulator of the innate immune system
PUBLISHED
Keywords: Myeloid KLF2; Myeloid KLF2; Genes & Society; Immunology, Inflammation & Infection; International Development